2005
DOI: 10.1248/bpb.28.271
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Coffee on Conjugation Reactions in Human Colon Carcinoma Cells

Abstract: We examined the effect of coffee on conjugation reactions in the human colon carcinoma cell line, Caco-2. After supplementing Caco-2 cultures with both 1-naphthol (200 m mM) and various concentrations of coffee, the accumulation of 1-naphthyl sulfate and glucuronide in the growth medium was determined by analytical HPLC over a 24-h period. A strong reduction in sulfo-conjugation (Ͻ50% of the control value) was observed in cells treated with coffee (IC 50 ‫,)%3.4؍‬ but no effect on glucuronic acid conjugation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
1
15
1
3
Order By: Relevance
“…The cDNA levels were normalized by b-actin, assessed by quantitative real-time PCR as described previously. 6) Quantitative real-time-PCR was performed with an ABI-Prism 7700 thermal cycler using a SYBR green PCR core reagent kit (Applied Biosystems, Wharmington, U.K.). Calculations of the initial amounts of mRNA were performed according to the cycle threshold method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cDNA levels were normalized by b-actin, assessed by quantitative real-time PCR as described previously. 6) Quantitative real-time-PCR was performed with an ABI-Prism 7700 thermal cycler using a SYBR green PCR core reagent kit (Applied Biosystems, Wharmington, U.K.). Calculations of the initial amounts of mRNA were performed according to the cycle threshold method.…”
Section: Methodsmentioning
confidence: 99%
“…Previously we have investigated such herb-drug interactions at the level of conjugation. 5,6) We have also recently established an assay system for conjugation reactions of 1-naphthol using a human adenocarcinoma cell line, Caco-2.7) In our current study, to elucidate the possible interaction of both turmeric and curcumin with the conjugation pathways in cells, which in many cases are involved in the activation of procarcinogens, we measured their effects on the conjugation activity of 1-naphthol in Caco-2 cells. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24) However, our current study showed that coffee strongly inhibits in vitro UGT activity of TR-TBT cells. This discrepancy might be due to the species difference of UGT enzyme structures between human and rat, or due to the difference of assay conditions.…”
Section: Discussionmentioning
confidence: 52%
“…11 Besides a minor decreased distal colon cancer risk among coffee consuming men, we found no significant protective effect of coffee in the present study. It is hypothesized that the possibly protective effect of coffee against CRC found in some studies may be related to antioxidant and antimutagenic effects of phenolic compounds (mainly chlorogenic acid), 6,33 inhibition of colon cancer cell growth by caffeine, 8,9 and cafestol and kahweol mediated reduction of bile acid synthesis 2,34,35 and inhibition of CYP1A2 and NAT2 activity. [36][37][38][39] In addition, caffeine may specifically protect against distal colon cancer by increasing the motility of the distal colon and, as a consequence, lowering carcinogen exposure of colonic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%